Canonical WNT signaling regulates development of bovine embryos to the blastocyst stage - Denicol, Anna C.; Dobbs, Kyle B.; McLean, Kanyon M.; Carambula, Silvia F.; Loureiro, Barbara [UNESP]; Hansen, Peter J. (Springer Nature, 2013)
Objectives were to evaluate the role of canonical WNT signaling in development of the preimplantation embryo. Signaling was activated with 2-Amino-4-(3,4-(methylenedioxy)benzylamino)-6-(3-methoxyphenyl)pyrimidine (AMBMP) and inhibited with Dickkopf-related protein 1 (DKK1). Treatment of bovine embryos with AMBMP at day 5 after insemination decreased development to the blastocyst stage at day 7 and reduced numbers of trophectoderm and inner cell mass cells. At high concentrations, AMBMP caused disorganization of the inner cell mass. DKK1 blocked actions of AMBMP but did not affect development in the absence of AMBMP. Examination of gene expression in day 6 morulae by microarray revealed expression of 16 WNT genes and other genes involved in WNT signaling; differences in relative expression were confirmed by PCR for 7 genes. In conclusion, the preimplantation embryo possesses a functional WNT signaling system and activation of the canonical pathway can inhibit embryonic development.
Keywords: 1,3 benzodioxole derivative; 2 amino 4 (3,4 (methylenedioxy)benzylamino) 6 (3 methoxyphenyl)pyrimidine; 2-amino-4-(3,4-(methylenedioxy)benzylamino)-6-(3-methoxyphenyl)pyrimidine; pyrimidine derivative; signal peptide; Wnt protein; animal; animal embryo; artificial insemination; blastocyst; cattle; chemistry; cytology; drug effect; drug potentiation; embryo development; female; gene expression regulation; genetics; metabolism; Wnt signaling pathway; Animals; Benzodioxoles; Blastocyst; Cattle; Embryo, Mammalian; Embryonic Development; Female; Gene Expression Regulation, Developmental; Insemination; Intercellular Signaling Peptides and Proteins; Pyrimidines; Wnt Proteins; Wnt Signaling Pathway